KORELASI TINGKAT PENDIDIKAN ORANG TUA DENGAN PRESTASI BELAJAR IPS SMPN 7 SUNGAI RAYA - Sari Sekar Wangi; Nuraini Asriati; Sri Buwono (Universitas Tanjungpura, 2020)
Abstract This research aims to determine the relationship of parents' education level with social studies learning achievement in class VIII at SMP Negeri 7 Sungai Raya. This research uses a quantitative approach with this type of research is ex post facto research. The population of this study was 138 students. How to take samples using the formula Isaac and Michael with an error rate of 10% to obtain 46 Responden. The sampling technique is done randomly (Simple Random Sampling). The variables studied were Parental Education Level (X) with Social Studies Learning Achievement (Y). Data collection uses questionnaires and documentation. Instrument validation uses expert judgment and reliability with internal consistency using the Cronbach Alpha Technique. The analysis technique used is Product Moment Correlation. Based on the analysis of the data the researchers conducted, it was concluded that: 1) The level of education of parents of Kalas VIII had a moderate category with the data acquisition of 31 students (67.4%) in that category, 2) Learning achievement of social studies subjects was obtained by 27 students ( 58.7%) students have moderate achievement. 3) The magnitude of the Relationship between Parents' Education Level and Social Studies Learning Achievement in VIII grade of SMP Negeri 7 Sungai Raya is strongly correlated, with a significance level of 5%, r values greater than r tables (0.654> 0.291). Keywords: parental education level, learning achievement, social studie